STRATEGIES FOR THE EFFECTIVE USE OF BUDGETARY AND NON-BUDGETARY FUNDS IN HIGHER EDUCATIONAL INSTITUTIONS (World Conference on Social Sciences, Law and Public Policy, 2026)
Effective financial management is a cornerstone of sustainable development in higher educational institutions. Universities face increasing pressures to maintain academic quality, conduct innovative research, and provide modern student services, all while operating within constrained budgets. Consequently, strategies for the effective use of both budgetary and non-budgetary funds have become essential to ensure financial stability, operational efficiency, and long-term institutional growth.